Technological and microbiological evaluation of different storage conditions of par-baked bread. (September 2020) - Debonne, Els; De Leyn, Ingrid; Vroman, Annemarie; Spaepen, Griet; Van Hecke, Marina; Ruyssen, Tony; Eeckhout, Mia
Abstract: Par-baking contributes to the extension of the physico-chemical and microbiological shelf-life of bread. Moreover, it adds convenience as par-baked (PB) breads can be full-baked on demand, providing fresh bread at any time of the day. In this study, different storage conditions of unfrozen PB bread (95% pre-baked) were investigated as an alternative for modified atmosphere packaging (MAP). These included the use of a FLEXBAKER-UV storage unit with 90 or 95% relative humidity (RH) and a traditional refrigerator. The physico-chemical and microbiological quality of PB bread before and after full-baking and storage was assessed, as well as the hygienic level of the storage conditions. Results showed that storage of PB breads in a FLEXBAKER-UV unit can limit moisture loss of the breads, resulting in a similar bread quality as in the case of MAP breads. Additionally, storage in a FLEXBAKER-UV unit with regulated RH overcomes the disadvantages of storage in a refrigerator, such as moisture loss and volume reduction. Storage of PB breads in a FLEXBAKER-UV with 90% RH, 3 °C and UV-air treatment extended mould-free shelf-life up to 3 weeks and can be a good alternative for MAP. Highlights: Ambient and chilled storage temperature has no influence on retrogradation of unfrozen PB bread 48h after full-baking. Retrogradation profile was equal for all stored PB breads 48h after full-baking. UV-air treatment significantly reduced the level of airborne moulds in the storage environment. A FLEXBAKER unit with 90% RH, 3 °C and UV-air treatment extended mould-free shelf-life of PB breads up to 3 weeks. FLEXBAKER-UV conditions provide good physicochemical and microbiological quality of PB bread.